IMPLEMENTASI PROGRAM PENDIDIKAN ANAK USIA DINI (Studi Komparatif Pada Taman Kanak-Kanak yang Terakreditasi dan Tidak Terakreditasi di Kelurahan Mantuil Kecamatan Banjarmasin Selatan) - Mega Pardosi; Widyakanti Widyakanti; M. Nur Iman Ridwan (Universitas Lambung Mangkurat, 2019)
Early Childhood Education Programs is a government way to create human resources are ready to compete in the era of globalization. The purpose of this research is to find (1) the implementing of early childhood education programs, especially in Mantui Village, Sub-district South Banjarmasin, and (2) what are the constraints of implementing process. The result of research is (1) implementation early childhood education there are not according to the standards listed in Permendiknas No.58 tahun 2009, and based on the results in the field, accredited kindegarten, the implementation is not accordance with the standards of early childhood education.(2) The most common of constraints is, human resources like most teachers have not scholar, and another constraint is facilities communication and information ,and infrastructure. The research recommend to(1) Banjarmasin Education Office :requiring teachers to graduate, not only for public servant but also private. (2) Kindergarten principal:giving priority to data management. (3) Kindergarten teachers : take more training provided by the government.